Reconstructing the arrival direction of neutrinos in deep in-ice radio detectors - Plaisier, Ilse; Bouma, Sjoerd; Nelles, Anna (European Physical Journal C: Particles and Fields, 2023)
In-ice radio detectors are a promising tool for the discovery of EeV neutrinos. For astrophysics, the implications of such a discovery will rely on the reconstruction of the neutrino arrival direction. This paper describes a first complete neutrino arrival direction reconstruction for detectors employing deep antennas such as RNO-G or planning to employ them like IceCube-Gen2. We will didactically introduce the challenges of neutrino direction reconstruction using radio emission in ice, elaborate on the detail of the algorithm used, and describe the obtainable performance based on a simulation study and discuss its implication for astrophysics.
CRIS-Team Scopus Importer:2023-07-14